Variasi Konsentrasi Asam Klorida (HCl) dan Lama Perendaman Slag Nikel dalam Proses Leaching serta Variasi Volume NH4OH untuk Mengendapkan Besi (Fe) - Wa Ode Sartifa; La Harimu; Wa Ode Mulyana (Sains: Jurnal Kimia dan Pendidikan Kimia, 2022)
This study aims to determine the optimal concentration and immersion time of hydrochloric acid (HCl) in the iron leaching process in nickel slag samples and to determine the optimal volume of ammonium hydroxide (NH4OH 6.5 M) to precipitate iron (Fe) from leaching results in slag samples nickel. This study used hydrochloric acid (HCl) 37% as a leaching agent with various concentrations of 20%, 25%, 30% and 37% in a volume of 25 mL with variations in curing time for 1, 2, 3 and 4 hours. The deposition process uses a precipitation method (gravimetric), where ammonium hydroxide solution (NH4OH 6.5 M) is used as a precipitating solution to precipitate iron with volume variations of 3, 4, 5 and 6 mL. Nickel slag samples in this study came from PT. Antam, Pomalaa. The weight of the sample used in this study was 2.5 grams. The results showed that the optimal concentration of HCl in iron leaching occurred at a concentration of 30% producing the most Fe2O3 deposits of 0,378 grams with a weight of Fe in Fe2O3 was 0.2646 grams and the percentage of Fe was 10,58%. Optimal leaching time occurs at 3 hours which produces the most Fe2O3 deposits of 0.378 grams with a weight of Fe in Fe2O3 is 0.2646 grams and the percentage of Fe is 10,58%. Optimal deposition of Fe occurs at a volume variation of 4 mL of ammonium hydroxide (NH4OH) resulting in the highest Fe2O3 precipitate of 0.384 grams with a weight of Fe in Fe2O3 is 0.2688 grams and the percentage of Fe is 10,75%.